2013
DOI: 10.1001/jamaoto.2013.2747
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Surgery for Oropharyngeal Cancer

Abstract: Objective To determine swallowing, speech and quality of life (QOL) outcomes following transoral robotic surgery (TORS) for oropharyngeal squamous cell carcinoma (OPSCC). Design Prospective cohort study. Setting Tertiary care academic comprehensive cancer center. Patients 81 patients with previously untreated OPSCC. Intervention Primary surgical resection via TORS and neck dissection as indicated. Main Outcome Measures Patients were asked to complete the Head and Neck Cancer Inventory (HNCI) pre-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(70 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…Only 28.2% required trimodality therapy (TORS followed by adjuvant CRT), which is less than the percentage of patients requiring trimodality therapy in some prior studies (43%−62%). 7,8,23,24 The relatively low frequency of trimodality therapy in our study population may partially explain the lower gastrostomy prevalence in the TORS group compared with the nonsurgical group, because the use of CRT is known to have adverse effects on swallowing function. 20 Although fewer patients undergoing TORS in our study received trimodality therapy compared with some prior studies, their survival was not inferior to that of patients undergoing RT/CRT in this matched analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Only 28.2% required trimodality therapy (TORS followed by adjuvant CRT), which is less than the percentage of patients requiring trimodality therapy in some prior studies (43%−62%). 7,8,23,24 The relatively low frequency of trimodality therapy in our study population may partially explain the lower gastrostomy prevalence in the TORS group compared with the nonsurgical group, because the use of CRT is known to have adverse effects on swallowing function. 20 Although fewer patients undergoing TORS in our study received trimodality therapy compared with some prior studies, their survival was not inferior to that of patients undergoing RT/CRT in this matched analysis.…”
Section: Discussionmentioning
confidence: 93%
“…The TORS system offers ready access to the oropharynx without external incisions for precise resections with minimal disruption of adjacent structures. 3 Studies have shown high survival rates, 46 low complication rates, 7 good swallowing function, 46,8 and excellent quality-of-life (QOL) 8 outcomes after TORS.…”
mentioning
confidence: 99%
“…[27] Disparity between the clinical AJCC/UICC TNM stage and survival in HPV-positive OPSCC[14,17] speaks to the need for a new staging paradigm. Moreover, there is significant discordance between clinical/radiological and pathologic nodal staging for head and neck carcinoma in general[28] and specifically for HPV-positive OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic pathologic parameters have been identified in surgical HPV-positive OPSCC cohorts. 1318, 23,27 To test these prognosticators, this study assembled a p16-positive OPSCC database from five centers. The study objectives were to assess:…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, the FDA approved the use of TORS to treat benign and malignant tumors of the head and neck. Initial results of patients who underwent TORS showed feasibility and low complication rates, good swallowing function and quality of life, as well as good oncologic outcomes [1-7]. Patients with oropharyngeal cancer who undergo TORS have decreased percutaneous endoscopic gastrostomy prevalence, a proxy for swallowing function, and at least comparable survival in comparison to matched oropharyngeal cancer patients treated with nonsurgical therapy [8].…”
Section: Introductionmentioning
confidence: 99%